2023
DOI: 10.3389/fpubh.2023.1091267
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes of health care workers about monkeypox virus infection in Southern Italy

Abstract: BackgroundThis present survey sought to investigate the level of knowledge and the attitudes pertaining the monkeypox (mpox) virus infection among a sample of health care workers (HCWs) in Italy, as well as the possible role of different factors on these outcomes.MethodsThe cross-sectional survey was performed from July through October, 2022 at four randomly selected hospitals located in Southern Italy.ResultsThe questionnaire was completed by 421 HCWs, for an overall 59% response rate. Less than two-thirds we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 48 publications
6
21
0
Order By: Relevance
“…At the earliest of the outbreak in May, 56.5% of Saudi Arabian physicians had not ever heard about monkeypox until the survey ( 24 ). Likewise, another study revealed that 3.5% of Italian healthcare workers did not know any of the answers on a monkeypox questionnaire and none of the healthcare workers answered all the questions correctly ( 28 ). These findings raise a crucial concern regarding the contemporaneity of healthcare workers around the world on monkeypox as well as future disease outbreaks and epidemics.…”
Section: Discussionmentioning
confidence: 99%
“…At the earliest of the outbreak in May, 56.5% of Saudi Arabian physicians had not ever heard about monkeypox until the survey ( 24 ). Likewise, another study revealed that 3.5% of Italian healthcare workers did not know any of the answers on a monkeypox questionnaire and none of the healthcare workers answered all the questions correctly ( 28 ). These findings raise a crucial concern regarding the contemporaneity of healthcare workers around the world on monkeypox as well as future disease outbreaks and epidemics.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 43 literature reviews and 82 editorials were excluded, as they were not suitable for inclusion in this speci c review. As a result of the rigorous study selection process, 10 papers [15][16][17][18][19][20][21][22][23][24] were deemed eligible and included in the review. It is noteworthy that no additional reports of newly included studies were found.…”
Section: Resultsmentioning
confidence: 99%
“…An overview of the demographic factors relevant to the research on the assessment of HCWs KAP regarding Mpox is shown in Table 2. The studies [15][16][17][18][19][20][21][22][23][24] used cross-sectional study designs to gather data and were carried out in various nations. The studies' samples, which ranged from 163 to 639 HCWs, were different in size.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations